2018
DOI: 10.1302/0301-620x.100b9.bjj-2017-1372.r1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multimorbidity on changes in health-related quality of life following hip and knee arthroplasty

Abstract: Multimorbidity adversely effects improvements in HRQoL following THA and TKA. Our findings are relevant to healthcare providers focused on the management of patients with chronic conditions and for administrators reporting and monitoring the outcomes of THA and TKA. Cite this article: Bone Joint J 2018;100-B:1168-74.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 186 publications
(384 reference statements)
3
24
0
Order By: Relevance
“…The SF‐12 has also been shown to be able to discriminate between patients with rheumatoid arthritis of the hands/wrists who have high pain and those with low pain (PCS ES = 0.81 and MCS ES = 0.33) . In addition, the responsiveness of the SF‐12 to a wide range of treatments and programs for musculoskeletal conditions has been reported .…”
Section: Medical Outcomes Study 12‐item Short Form Health Surveymentioning
confidence: 96%
“…The SF‐12 has also been shown to be able to discriminate between patients with rheumatoid arthritis of the hands/wrists who have high pain and those with low pain (PCS ES = 0.81 and MCS ES = 0.33) . In addition, the responsiveness of the SF‐12 to a wide range of treatments and programs for musculoskeletal conditions has been reported .…”
Section: Medical Outcomes Study 12‐item Short Form Health Surveymentioning
confidence: 96%
“…These differences have the potential to help illustrate how variations in patient selection (preoperative disease severity, age, sex, comorbidities) and processes of care delivery (for example public versus private funding) can affect rates of surgery and surgical outcomes. However, these comparisons need to be done thoughtfully, as confounding factors such as age, sex, body mass index, comorbidities 54 and socioeconomic status 55 among others may make comparisons difficult. 9 The use of different PROMs tools across registries also presents unique challenges, since robust ‘cross walk’ algorithms will need to be developed to allow for valid comparisons.…”
Section: Comparisons Of Proms Data Across Registriesmentioning
confidence: 99%
“…While PROMs cannot yet be used at the individual patient level to determine a cut point or appropriateness for surgery, 63 their collection in registries does allow for a better understanding of how other related factors such as age, sex, preoperative disease severity, generic QoL and comorbidities broadly affect the outcome of surgery at the population level. 54,64 This can help inform the individual decision-making process as the information can be incorporated into the clinical setting and, when counselling potential arthroplasty patients regarding surgery, reasonable expectations can be discussed based on fact rather than conjecture. 50 The inability to precisely predict appropriateness at the individual patient level using PROMs is related to poor questionnaire reliability at the individual level, the impact that patient demographics, diagnosis, expectations and comorbidities have on outcome and the lack of validation of PROMs for this purpose.…”
Section: Comparisons Of Proms Data Across Registriesmentioning
confidence: 99%
“…TKA and THA are common considerations for effective procedures for patients with advanced osteoarthritis [7,10]. Although using comorbidities to predict clinical outcomes has increased substantially in the past 20 years for patients undergoing TKA and THA [2,6,11,12], their relationship to the risk of revision is unclear. Moreover, most joint arthroplasty patients have a high prevalence of comorbidities, which can affect surgical outcomes, and previous studies have identified risk factors associated with lower implant survival [13].…”
Section: Introductionmentioning
confidence: 99%